'Yet All is Not Lost:' An Account and Defense of Ecological Conversion in Laudato Si'. (30th April 2018) - Morgan, Jeffrey
Abstract : In this essay I offer an account and defense of conversion in Laudato Si' . While Francis's call to conversion itself is brief, it is a crucial feature of the encyclical, providing a rationale for how individuals might make a radical break from the structural violence of the ecological crisis that deeply compromises moral agency in the Global North. This claim requires a defense because, as Willis Jenkins argues, appeals to conversion in environmental ethics typically assume a coherent moral theological framework, and the scale of environmental problems renders all such frameworks incapable of generating competent calls to conversion. Avoiding such frameworks, Jenkins nonetheless tacitly must appeal to conversion in his own pragmatic approach to environmental problems. But through an engagement with Francis and Jenkins, I argue that conversion is a conceptually unstable concept without something like Francis's normative framework to account for its possibility and for hope to be reasonable.